Pengaruh Modal, Jam Kerja, Dan Sumber Daya Manusia Terhadap Pendapatan Pedagang Kaki Lima Di Kelurahan Kenali Besar Kecamatan Alam Barajo Kota Jambi - Septiasari, Karina; Arsa, Arsa; Orinaldi, Mohammad (Otonomi, 2024)
The amount of income will be influenced by several factors including capital, working hours, and human resources. This study aims to determine how capital, working hours and human resources affect the income of street vendors in Kenali Besar Village, Alam Barajo District, Jambi City. The research method used is quantitative with the number of samples taken as many as 57 respondents. While collecting data with a questionnaire (questionnaire). Based on data analysis using instrument tests consisting of validity tests and reliability tests, classical assumption tests, hypothesis testing consisting of multiple linear regression tests, t tests, f tests, and R square tests. The results showed that: 1) Capital has a positive and significant effect on the income. 2) Working hours have no effect and are not significant to the income.3) Human Resources has a positive and significant effect on the income. 4) simultaneously Capital, Working Hours and Human Resources have a significant effect on the income.